Small airway function in predicting asthma control in preschool children - Liangqin Yi; Yan Zhao; Ziyao Guo; Qinyuan Li; Chunlan Qiu; Jingyi Yang; Sha Liu; Fangjun Liu; Ximing Xu; Zhengxiu Luo (Wiley, 2024)
Abstract Asthma control in children is often challenging. This retrospective cohort study aimed to investigate the potential contribution of small airway function in predicting asthma control within a 2‐ to 3‐month period following the initial diagnosis in preschool children with asthma. A total of 219 preschool children diagnosed with asthma were enrolled, and their follow‐up was conducted by pediatric pulmonary physicians. Clinical history and lung function results were collected for analysis. To identify risk factors associated with poor asthma control, a multivariable regression model was employed. Sixty‐nine of the patients (31.5%) exhibited poor asthma control. Poor adherence to therapy (14.5% vs. 6.0%, p = 0.038) and the presence of severe airway hyperresponsiveness (AHR) (20.6% vs. 1.6%, p < 0.001) were more prevalent in the group with poor control. Additionally, baseline forced expiratory volume in 1 s in predicting (94.5% vs. 101.4%, p = 0.001), forced expiratory flows (FEF)50% (66.1% vs. 86.0%, p < 0.001), FEF75% (60.9% vs. 75.3%, p = 0.001), and FEF25-75% (70.9% vs. 86.0%, p < 0.001) were significantly lower in the poorly‐controlled group than those of well‐controlled group. There was no significant difference in forced vital capacity in predicting (FVC%) between the two groups (92.4% vs. 96.7%, p = 0.093). Multivariable regression model unveiled initial severe AHR (OR 8.595, 95%CI 1.241-59.537, p = 0.021) and decreased FEF50% (OR 0.971, 95%CI 0.949-0.994, p = 0.012) were significantly associated with short‐term poor asthma control. Preschool children with asthma who exhibites initial severe AHR and/or decreased FEF50% faces an elevated risk of encountering poor asthma control during the subsequent 2-3 months.